Vestibular rehabilitation improves spontaneous nystagmus normalization in patients with acute unilateral vestibulopathy - Lacour, Michel; Lopez, Christophe; Thiry, Alain; Tardivet, Laurent (Frontiers in Rehabilitation Sciences, 2023)
Spontaneous nystagmus (SN) can be observed after acute unilateral vestibulopathy (AUVP). The slow phase eye velocity of the SN progressively decreases in darkness as the result of rebalanced neurophysiological activity between both vestibular nuclei, a process that can take several months. Although this compensatory process can occur spontaneously, there is poor evidence that vestibular rehabilitation (VR) can facilitate the process. We document the natural time course of SN reduction in patients with AUVP, as well as the effects of VR by means of a unilateral rotation paradigm. In a retrospective study (Study 1: n = 126 AUVP patients), we compared the time course of the SN reduction in patients with VR (n = 33) and without VR (n = 93). In a prospective study (Study 2: n = 42 AUVP patients), we compared the effects of early VR (n = 22; initiated within the first two weeks of symptoms onset) or late VR (n = 20; initiated after the second week of symptoms onset) on the time course of the SN reduction. Study 1 showed shorter median time of SN normalization in patients with VR compared to patients without VR (14 days and 90 days, respectively). Study 2 showed that AUVP patients with early and late VR had a similar time course of SN reduction. The SN slow phase eye velocity was significantly decreased as early as the end of the first VR session in both groups, and kept decreasing at each subsequent VR session. In the early VR group, 38% of the patients had slow phase eye velocity below 2°/s after the first VR session, 100% after the fifth session. Similar findings were observed in the late VR group. Taken together, these results indicate that VR with a unidirectional rotation paradigm speeds up the normalization of SN. This effect seems independent of the time between symptoms onset and commencement of VR, but early intervention is recommended to speed up the SN reduction.